Dissemination and Design of Standard Operating Procedure (SOP) Production and Distribution of Ground Coffee at CV. Coffee Taste of Persada, Pasuruan - Feni Kusumaning Arum; Riski Ayu Anggreini (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Coffee powder is one of the products favored by the public. Many industries produce these products, one of which is CV. Kopi Citarasa Persada. To gain an understanding of the importance of SOP, performance that is more systematic, efficient and running according to company goals, a socialization and design of the Standard Operating Procedure (SOP) for Robusta ground coffee production was carried out at CV. Kopi Citarasa Persada. By properly implementing the Standard Operating Procedure (SOP) in a company, it can help maintain the stability of employee performance and the quality of the products produced. Based on this activity the results obtained in the form of draft SOP for post-harvest handling, SOP for production process, SOP for product packaging, SOP for product storage, SOP for product sales, SOP for distribution and SOP for employee.